Augmented reality, virtual reality, and computer graphics : 7th International Conference, AVR 2020, Lecce, Italy, September 7-10, 2020, Proceedings.: 7th International Conference, AVR 2020, Lecce, Italy, September 7-10, 2020, Proceedings. Part I (2020) - Unknown
No abstract available